Relation of serum elastin peptide concentration to age, FEV1, smoking habits, alcohol consumption, and protease inhibitor phenotype: an epidemiological study in working men. Issue 11 (November 1992) - Frette, C; Wei, S M; Neukirch, F; Sesboüé, R; Martin, J P; Jacob, M P; Kauffmann, F
Abstract : BACKGROUND: In clinical investigations elastin peptide concentration has been proposed as one potential marker of lung elastin degradation. No epidemiological study has yet confirmed this hypothesis. METHODS: The relation of elastin peptide concentration to some factors closely related to pulmonary emphysema (age, smoking habits, FEV1 alpha protease inhibitor (PI) phenotype) and to alcohol consumption was examined in an epidemiological study of 310 working men. The elastin peptides used for obtaining antibodies and as reference in an ELISA assay were prepared from chemically hydrolysed elastin. RESULTS: The elastin peptide concentration significantly decreased with age from 2.92 (1.54) micrograms/ml among subjects younger than 30 years to 2.18 (1.14) micrograms/ml among subjects older than 50. Elastin peptide concentration did not differ with smoking habits and was clearly unrelated to FEV1. A lower elastin peptide concentration was observed in all groups of subjects with a protease inhibitor phenotype other than PI MM (PI FM, IM, MP, MS, MZ, and S phenotypes). CONCLUSIONS: The results cast doubts on the usefulness of the elastin peptide concentration as a marker of lung destruction in middle aged, predominantly healthy men. Blood elastin peptide concentration may reflect both elastin degradation and resynthesis. The results of this analysis suggest that several factors (age, alcohol consumption, non-PI MM phenotype) may be associated with decreased resynthesis of lung elastin. Further studies, conducted in various age groups and including estimates of the degree of lung destruction, are needed to unravel the mechanisms underlying lysis and resynthesis of lung elastin.